Identification, distribution and geochemical significance of four rearranged hopane series in crude oil. (December 2019) - Xiao, Hong; Li, Meijun; Wang, Wenqiang; You, Bing; Liu, Xiaoqiang; Yang, Zhe; Liu, Jiguo; Chen, Qingyao; Uwiringiyimana, Martin
Highlights: Four rearranged hopane series were simultaneously detected in oil samples. E and Nsp series have slower formation rates than the D series. The Ts series is generated from multiple biological sources. The four rearranged hopane series are highly resistant to microbial degradation. Calculated Gibbs free energy (△G) show the order C30 D > C30 H > C30 E. Abstract: Four rearranged hopane series were simultaneously detected in oils from the Muglad Basin, one of several rift basins on the Central African Shear Zone (CASZ). The series are identified as having the structure of 17α(H)-diahopane (D series), 18α(H)-neohopane (Ts series), early eluting rearranged hopane (E series) and 21-methyl-28-norhopanes (Nsp series). The four rearranged hopane series exhibit strong positive correlations. The slope and intercept of the linear equation in plots of C29 D/C29 H vs C30 D/C30 H are 1.10 and 0.003 respectively, possibly implying identical biological origins and formation mechanisms. The relatively low slope (<0.80) and intercept (<0.07) in both C30 E/C30 H vs C30 D/C30 H and C29 Nsp/C29 H vs C29 D/C29 H suggest that E and Nsp series have similar biological origins as D series, but form at a slower rate following different rearrangement mechanisms. Both the Nsp and E series require the shifting of two methyl groups from their precursors, whereas the D series have only one methyl migration from C-18 to C-17. The extremely high values of slope (1.42) and intercept (0.427) in a plot of C29 Ts/C29 H vs C29 D/C29 H probably indicates that the Ts series is more easily generated than other rearranged hopane series and possibly has multiple biological sources, such as contributions from diplopterol and/or diploptene. Furthermore, C30 E, C30 D, C29 Nsp and Ts are enriched relative to regular hopanes in severely biodegraded oil samples owing to their greater resistance to microbial degradation, and/or additional sources of rearranged hopanes from bacterially reworked terrigenous organic matter. Based on relative Gibbs free energies ( Δ G ) calculated by density functional theory (DFT), the thermodynamic stabilities of C30 isomers follow the order C30 D > C30 H > C30 E.